Awareness of risk factors and warning symptoms and attitude towards gastric cancer screening among the general public in China: a cross-sectional study - Qi Liu; Wen Wang; Xi Zeng; Ruo-lin Huang; Yan-jin Huang; Ying-hui Huang; Ying-xin Wang; Qing-hong Fang; Guoping He; Ying Zeng (BMJ Open)
Objectives This study aimed to assess the knowledge of risk factors and warning symptoms and attitude towards gastric cancer screening among the general population in China.Setting Hunan province, ChinaParticipants Individuals aged older than 18 years were recruited using a cluster sampling method.Design A cross-sectional study, and a pretested structured questionnaire was used to assess participants’ awareness of gastric cancer.Primary and secondary outcome measures Knowledge level of risk factors and warning symptoms of gastric cancer, gastric cancer screening attitude, sociodemographic factors associated with gastric cancer knowledge and screening behaviour.Results This study comprised 1200 participants with a mean age of 40.31 (SD 16.73) years, of whom 622 (51.8%) were women. The mean score for gastric cancer knowledge was 8.85/22 (SD 6.48). There were 47.0% of the participants who had a low knowledge level about the risk factors and warning symptoms of gastric cancer. In total, 83.8% believed screening is helpful for early detection of gastric cancer, and 15.2% had undergone gastric cancer screening. The most common reason for not undergoing screening was having ‘no symptoms’ (63.0%), followed by ‘fear of undergoing gastroscopy’ (38.1%). Independent factors related to lower knowledge levels included male sex, living in rural areas, lower educational level, working as a farmer and without a family history of gastric cancer (p<0.05). Factors independently associated with screening behaviour included white-collar employment, higher income and having upper gastrointestinal tract diseases (p<0.05).Conclusions In China, people have poor knowledge about risk factors and warning symptoms of gastric cancer, but a majority have a positive attitude towards the benefits of gastric cancer screening. Being asymptomatic and having a fear of gastroscopy were the main self-reported reasons for not undergoing screening. These results highlight the urgent need for educational campaigns to improve gastric cancer awareness.